2012
DOI: 10.1016/j.clinph.2011.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and segmental excitability during fatiguing contractions of the soleus muscle in humans

Abstract: Objective The aim of this study was to examine the cortical and segmental excitability changes during fatigue of the soleus muscle. Methods Ten healthy young subjects performed 45 plantar flexion maximal voluntary contractions (MVCs) (7-s on/3-s off) in 9 epochs of five contractions. Motor evoked potentials (MEPs) using transcranial magnetic stimulation and H-reflexes were assessed during the task. Results The torque and the soleus EMG activity both showed the greatest decline during the 1st epoch, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 52 publications
3
35
1
Order By: Relevance
“…In this context, the reduction in CMEPs was due to reduced excitability of spinal motoneurons during a fatiguing task. This finding is consistent with the study of Iguchi and Shields (2012) who also reported decreased spinal excitability of the soleus muscle during intermittent maximal 14 contractions. In both of these studies, increased MEP size was considered to be a compensatory mechanism of the motor cortex, in an attempt to compensate for the reduction in motoneuron excitability.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this context, the reduction in CMEPs was due to reduced excitability of spinal motoneurons during a fatiguing task. This finding is consistent with the study of Iguchi and Shields (2012) who also reported decreased spinal excitability of the soleus muscle during intermittent maximal 14 contractions. In both of these studies, increased MEP size was considered to be a compensatory mechanism of the motor cortex, in an attempt to compensate for the reduction in motoneuron excitability.…”
Section: Discussionsupporting
confidence: 83%
“…This pathway most likely compensates at least part of the effect of supraspinal fatigue (Tanaka and Watanabe 2012;Taylor et al 1996). In the current experiment, the decreased MEP size during the sets could be due to decreased voluntary drive caused by decreased facilitation or increased inhibition of the cortical output neurons, or inhibition of the motoneurons at the spinal level (Butler et al 2003;Iguchi and Shields 2012). Unfortunately, cervicomedullary stimulation, which is thought to be the only valid measure for spinal sensitivity, could not be conducted in this experiment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies have investigated changes in the amplitude of the H-reflex during various types of contractions of the soleus muscle [56,57]. In one study, Duclay and Martin [58] obtained the lowest value of the Hmax/Mmax ratio during the eccentric contraction; whereas the isometric and concentric contractions showed a similar ratio.…”
Section: Applications Of the Hoffman's Reflex Measurementmentioning
confidence: 99%
“…Phadke et al [83] also observed the effect of a 20-minute walk on the decrease in the amplitude of the H-reflex due to the presynaptic inhibition. Studies also show that the amplitude of the H-reflex may return to its resting values as quickly as a minute following exercises on a cycloergometer [57].…”
Section: Applications Of the Hoffman's Reflex Measurementmentioning
confidence: 99%